ANALYSIS OF THE POSSIBILITY OF USING WI-FI TECHNOLOGY IN THE TRANSPORT NETWORK TO IMPROVE TRAFFIC AND PEDESTRIAN SAFETY - ПАВЛЮЧЕНКО, В. А.; МАКАРЕНКО, В. В. (Technologies and Engineering, 2023)
Purpose. Conduct an analysis of the possibility of using W-Fi technology in the city’s transport network in order to improve the safety of pedestrians and vehicles and draw conclusions about the feasibility of using this technology in the transport network. Methodology. Urban infrastructure modeling and signal level propagation analysis in the Altair WinProp software simulator. Conducting data channel quality analysis by testing packet loss and bandwidth at different signal levels. Analysis of the quality of data transmission at different signal levels was carried out using a Mikrotik Wi-Fi router and a laptop with a Wi-Fi module. Findings. As a result of the research, modeling of the city infrastructure was performed to analyze the spread of the signal level from Wi-Fi access points. The analysis of signal level propagation from Wi-Fi access points was carried out in the Altair WinProp software simulator. In the course of the research, it was established that in order to build a reliable "seamless" network, it is necessary to create a coverage in which the signal level was not less than -70 dBm. It has been established that four Wi-Fi access points, with a transmitter power of +21 dBm, installed at a distance of about 50 m from each other will be sufficient to ensure reliable communication of road users at a distance of up to 50 m from the intersection. Originality. The limit level of the signal from the Wi-Fi access point, at which the number of packet losses will be minimal, was found for the construction of a "seamless" coverage for the transport network. The feasibility of using Wi-Fi technology for transport and pedestrians in a smart city is analyzed. Practical value. The results of research and modeling of signal level propagation from Wi-Fi access points can be used to create a "seamless" coverage for the transport infrastructure of a smart city.